Chapter 16 Surgery and Emotion The Era Before Anaesthesia - Brown, Michael (Springer Nature, 2018)
In this chapter I have endeavoured to demonstrate the ways in which an approach that takes the emotions seriously might nuance and complicate our understandings of the history of pre-anaesthetic surgery. In general, historians have tended to focus on the operations of surgical dispassion, or what we might now term clinical detachment. What this research suggests, however, is that compassion and emotional expression played a surprisingly important role in shaping the cultures of early nineteenth-century operative surgery as well as the identities of its practitioners. In the decades immediately preceding the advent of anaesthesia, pain became a central concern of surgical discourse and the response to this concern was shaped by the cultures of sentiment and sensibility. However, this culture of compassion was no 'natural' reaction to a self-evident problem. Rather, it was a culturally and historically contingent phenomenon which could be harnessed to the ideologies and ambitions of medical reform. In the hands of men like John Bell and Thomas Wakley, the image of the surgeon as a man of refined and honest sentiment was linked to a critique of the medical and surgical ancien regime, providing an idealised representation of a more expert, meritocratic and altruistic profession.